Performance and emission of a spark-ignition engine using gasoline-plastic pyrolysis oil blends - Sunaryo Sunaryo; Suyitno Suyitno; Zainal Arifin; Muji Setiyo (Mechanical Engineering for Society and Industry, 2024)
In response to the problem of plastic waste, this study investigates the conversion of PET waste plastics into Pyrolysis Plastic Oil (PPO) as an environmentally sustainable alternative energy source, aiming to tackle the pressing issue of plastic waste accumulation. Accordingly, the research comprehensively evaluates the physicochemical properties of PPO, examines its impact on engine performance, and determines the optimal concentrations for blending with gasoline. The investigation uncovers the potential of PPO through precise material preparation involving PET plastic waste pyrolysis, employing meticulous testing and analysis for comprehensive insights. Engine testing, conducted on a 125 cc, 4-stroke motorized vehicle, scrutinizes power, torque, and exhaust emissions under various PPO and gasoline blends. The findings reveal distinctive relationships between PPO ratios and engine behavior, emphasizing the need for nuanced fuel blending. The examination extends to fuel consumption and specific fuel consumption (SFC) testing, highlighting PPO's superior SFC. Exhaust emission testing demonstrates reduced emissions with heightened PPO concentration, showcasing its positive environmental impact. The results contribute valuable insights into PPO's viability as an alternative fuel source and its potential role in mitigating plastic waste. A comparative analysis with existing literature enriches our understanding of the field, emphasizing the need for careful consideration in fuel formulation. While PPO may not achieve performance parity with conventional gasoline, its environmental benefits and efficient waste utilization underscore its significance for a sustainable future. Further research is encouraged to optimize PPO properties and blending ratios, paving the way for an eco-friendlier energy landscape.